Propriedades fotocatalíticas de óxidos mistos preparados por oxidação eletrolítica a plasma (PEO) - Pissolitto, Yasmin Bastos (Universidade Federal de São Carlos, 2021)
The pollution of drinking water due to industrial activity in recent decades can have consequences for the supply and health of the population. Advanced oxidative processes (AOPs) such as heterogeneous photocatalysis are investigated in the literature for the development of devices and technologies for the treatment of water and industrial effluents. In this work, a semiconductor was developed and its optical and electronic properties were investigated, which allow the application of this material as a heterogeneous photocatalyst in wastewater treatment. Aluminum samples in an electrolyte solution with and without the presence of niobium ammoniacal oxalate (NAO) were anodized by Plasma Electrolytic Oxidation (PEO) for the adhesion of niobium to the surface of the oxide formed to form the semiconductor. The samples were anodized under galvanostatic mode, with a current density of 10 mA/cm2, for one hour. Using the factorial design tool, the effect of OAN concentration and initial temperature of the electrolyte solution variables on some investigated responses was investigated. Responses of electrochemical synthesis, morphology, composition and band-gap energy of semiconductors obtained from synthesis chronopotentiograms, micrographs, composition by dispersive energy spectroscopy and diffuse reflectance were investigated. It was possible to observe the influence of the variables, in particular the variation in the concentration of the electrolyte solution. Photodegradation tests were performed using methylene blue (MB) and rhodamine B (RhB) solutions at concentrations of 2.5 mg/L and volumes of 5 mL per semiconductor sample under UV radiation. For tests with MB, the increase in temperature and concentration of the electrolyte showed a greater response effect on the heterogeneous photodegradation of MB. It was not possible to reuse semiconductors in MB photodegradation even after cleaning with water, alcohol and acetone. As for the photodegradation of RhB, the sample synthesized under lower conditions of concentration and temperature showed greater photodegradation in the first use after 4 hours under UV light. As for the reuse of samples after cleaning with water, only the sample synthesized under higher conditions of temperature and electrolyte concentration showed significant results in relation to error for up to 3 reuses in the photodegradation of RhB. The study carried out demonstrated the effect of the variables temperature and concentration of the electrolyte on the morphology, composition, and potential for use in heterogeneous photocatalysis.
Photocatalytic properties of mixed oxides prepared by plasma electrolytic oxidation (PEO)
Keywords: Alumínio; Nióbio; Oxidação eletrolítica a plasma; Fotocatálise heterogênea; Aluminum; Niobium; Plasma electrolytic oxidation; Heterogeneous photocatalysis; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::CINETICA QUIMICA E CATALISE; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS::MATERIAIS E COMPONENTES SEMICONDUTORES